Pseudomonas aeruginosa N-3-Oxo-Dodecanoyl-Homoserine Lactone Impacts Mitochondrial Networks Morphology, Energetics, and Proteome in Host Cells - Josephson, Henrik; Ntzouni, Maria; Skoglund, Camilla; Linder, Stig; Turkina, Maria V.; Vikström, Elena (Frontiers in Microbiology, 2020)
Mitochondria play crucial roles in cellular metabolism, signaling, longevity and immune defense. Recent evidences have revealed that the host microbiota, including bacterial pathogens, impact mitochondrial behaviors and activities in the host. The pathogenicity of Pseudomonas aeruginosa requires quorum sensing (QS) cell-cell communication allowing the bacteria to sense population density and collectively control biofilm development, virulence traits, adaptation and interactions with the host. QS molecules, like N-3-oxo-dodecanoyl-L-homoserine lactone (3O-C12-HSL), can also modulate the behavior of host cells, e.g. epithelial barrier properties and innate immune responses. Here, in two types of cells, fibroblasts and intestinal epithelial cells, we investigated whether and how P. aeruginosa 3O-C12-HSL impacts the morphology of mitochondrial networks and their energetic characteristics, using high-resolution transmission electron microscopy, fluorescence live-cell imaging, assay for mitochondrial bioenergetics, and quantitative mass spectrometry for mitoproteomics and bioinformatics. We found that 3O-C12-HSL induced fragmentation of mitochondria, disruption of cristae and inner membrane ultrastructure, altered major characteristics of respiration and energetics, and decreased mitochondrial membrane potential, and that there are distinct cell-type specific details of these effects. Moreover, this was mechanistically accompanied by differential expression of both common and cell-type specific arrays of components in the mitochondrial proteome involved in their structural organization, electron transport chain complexes and response to stress. We suggest that this effect of 3O-C12-HSL on mitochondria may represent one of the events in the interaction between P. aeruginosa and host mitochondria and may have an impact on the pathogens strategy to hijack host cell activities to support their own survival and spreading.